Design and Implementation of Amba Based AHB to APB Bridge Protocol - D. Venkanna Babu; S.N.V. Dinesh; K. Uma Prasad; T. L. Avinash (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
In this paper, we present a comprehensive study on the design and implementation of an AHB to APB bridge protocol for efficient data transfer in complex system-on-chip (SoC) architectures. The Advanced High-performance Bus (AHB) and Advanced Peripheral Bus (APB) protocols are fundamental components in modern embedded systems, facilitating communication between high-speed components and slower peripherals. Our bridge protocol aims to seamlessly integrate these protocols, enabling smooth and efficient data exchange between different devices within the system. We discuss the rationale behind the need for such a bridge, highlighting its role in optimizing system performance and power consumption. Furthermore, we explore the impact of modifying the states of the APB Finite State Machine (FSM) on achieving advanced features such as burst 8, 16, and wrap logic, enhancing the versatility and functionality of the bridge protocol. Additionally, we provide insights into the implementation details, including the design considerations and methodology employed. Finally, we discuss potential future enhancements and real-world applications of the AHB to APB bridge protocol, underscoring its significance in advancing SoC design and functionality.